Symposium 1: Translating Networked Learning: Un-tying Relational Ties Online - Enriquez, Judith Guevarra (Proceedings of the International Conference on Networked Learning, 2006)
This paper explores the social network of learning beyond a functional understanding of social relations. It describes and interprets the realities of networked learning within a particular postgraduate course in an English university setting beyond the network analyses and graphical simulations of a software application. The use of social network analysis (SNA) alongside content analysis has dominated to some extent current studies in the field of networked learning. In particular, SNA has been used to analyse response relations among participants in online discussions in terms of, for example, centrality or strong and weak ties. Beyond relational ties, this paper presents a partial possibility and a different performativity of a network of learning, wherein the strength in relational ties does not only come from notions of centrality and frequency of responses, but also from the relational effects of multiple technical and social arrangements and engagements beyond the online environment as negotiated and anticipated among those involved.